2019
DOI: 10.56369/bac.2993
|View full text |Cite
|
Sign up to set email alerts
|

Las garrapatas como vectores de enfermedades zoonóticas en México

Abstract: sin resumen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Rhipicephalus microplus (Acari: Ixodidae) are prevalent in livestock and have been shown to act as vectors for pathogens with zoonotic potential among which are the pathogens that cause the above‐mentioned diseases: anaplasmosis and babesiosis. For instance, in the United States, 4151 cases of human granulocytic anaplasmosis were recorded in 2016 and 2358 cases of babesiosis in 2017 (CDC, 2020; Martins et al, 2020; Pérez de León et al, 2020; Rodríguez‐Vivas et al, 2019), while during 2019, 50,865 cases of tick‐borne diseases were reported (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rhipicephalus microplus (Acari: Ixodidae) are prevalent in livestock and have been shown to act as vectors for pathogens with zoonotic potential among which are the pathogens that cause the above‐mentioned diseases: anaplasmosis and babesiosis. For instance, in the United States, 4151 cases of human granulocytic anaplasmosis were recorded in 2016 and 2358 cases of babesiosis in 2017 (CDC, 2020; Martins et al, 2020; Pérez de León et al, 2020; Rodríguez‐Vivas et al, 2019), while during 2019, 50,865 cases of tick‐borne diseases were reported (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%